2019
DOI: 10.3390/min9120732
|View full text |Cite
|
Sign up to set email alerts
|

Britholite Group Minerals from REE-Rich Lithologies of Keivy Alkali Granite—Nepheline Syenite Complex, Kola Peninsula, NW Russia

Abstract: The Keivy alkali granite-nepheline syenite complex, Kola Peninsula, NW Russia, contains numerous associated Zr-REE-Y-Nb occurrences and deposits, formed by a complex sequence of magmatic, late-magmatic, and post-magmatic (including pegmatitic, hydrothermal, and metasomatic) processes. The REE-rich lithologies have abundant (some of economic importance) and diverse britholite group minerals. The REE and actinides distribution in host rocks indicates that the emanating fluids were alkaline, with significant amou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Although this mismatch can be often attributed to analytical uncertainties, our geologically reasonable conditions employed in the synthesis described above indicate that an oxybritholite component may contribute to the mismatch. Silica-deficient and low-totals britholites observed in some localities are potential hosts for undetected carbonates. In some cases, apatite–britholite analyses plot consistently below the 1:1 line on a Ca+P–REE+Si plot, , which could be easily explained by the presence of carbonate substituting for silicate. We expect this to occur mostly in carbonatite-associated fluorapatite. , …”
Section: Discussionmentioning
confidence: 99%
“…Although this mismatch can be often attributed to analytical uncertainties, our geologically reasonable conditions employed in the synthesis described above indicate that an oxybritholite component may contribute to the mismatch. Silica-deficient and low-totals britholites observed in some localities are potential hosts for undetected carbonates. In some cases, apatite–britholite analyses plot consistently below the 1:1 line on a Ca+P–REE+Si plot, , which could be easily explained by the presence of carbonate substituting for silicate. We expect this to occur mostly in carbonatite-associated fluorapatite. , …”
Section: Discussionmentioning
confidence: 99%
“…The loss of LREE relative to HREE in the chevkinite-(Ce) and aeschynite-(Y) as alteration proceeded is consistent with their greater solubility in CO 2 -rich fluids (Smith et al [15]). Earlier, Zozulya et al [16] suggested, from their study of the britholite-group minerals, that they had crystallized at relatively high F activity and low CO 2 /H 2 O ratios. Zozulya et al [5] found that fergusonite in the pegmatite has [La/Nd]cn = 0.03-1.2, indicating relatively high H 2 O/CO 2 in fluids.…”
Section: Hydrothermal Fluidsmentioning
confidence: 99%
“…Representative analyses of silicates dominated by light rare earth elements associated with chevkinite-Ce are listed in Table S13. Atomic proportions recalculated from formulae based on eight cations plot along the britholite-apatite exchange vector (Ca + P) =~7.86 − (Re + Si) [29]. The Re + Si values between 6.40 and 6.64 indicate 82-85.1 mol.% britholite-Ce component in the Ca-Ce-silicate from syenite HP-3 (Figure 9a).…”
Section: Britholite-cementioning
confidence: 99%